A 47-kDa human nuclear protein recognized by antikinetochore autoimmune sera is homologous with the protein encoded by RCC1, a gene implicated in onset of chromosome condensation. - Bischoff, F R (1990)
Several autoimmune sera from patients with Raynaud phenomenon decorated mammalian kinetochores and bound to a 47-kDa protein on immunoblots of nuclear lysates. Antibody affinity-purified from immunoblots of the 47-kDa band recognized kinetochores, but due to crossreaction with an 18-kDa protein, localization remains elusive. We used one of these sera to purify the antigen from HeLa cells synchronized in mitosis as a noncovalent complex with a 25-kDa protein. The antigen was released from DNA by intercalation with 25 mM chloroquine. Ion-exchange chromatography yielded the pure complex with an apparent molecular size of 68 kDa, which was separated into its components by gel filtration in 6 M guanidinium chloride. Upon two-dimensional gel electrophoresis the 47-kDa protein gave two main spots of pI 6.6 and 6.7, respectively. Posttranslational modification is indicated by additional antigenic spots, by lack of a free alpha-amino group, and by chromatographic behavior of peptides on reversed-phase chromatography. The amino acid sequence for 205 residues of the 47-kDa protein has been established. This sequence is highly homologous with the translated reading frame of RCC1, a gene reportedly involved in regulating onset of mammalian chromosome condensation.